KURT JANISCH’S POWER AND SEXUALITY IN ELFRIEDE JELINEK’S GREED (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2014)
KURT JANISCH’S POWER AND SEXUALITY IN ELFRIEDE JELINEK’S GREED Annisa Firdausi English Literature, Faculty of Languages and Arts, Surabaya State University firdausi.annisa19@gmail.com Drs. Much. Khoiri, M.Si English Department, Faculty of Languages and Arts, Surabaya State University much_choiri@yahoo.com Abstrak Kekuasaan sering didefinisikan sebagai kemampuan seseorang yang kuat untuk mendapatkan keinginannya atas kehendak orang yang tidak berdaya. Orang-orang yang memiliki kekuasaan dapat menggunakan kekuasaan mereka untuk mengambil keuntungan untuk mereka sendiri, mengontrol orang lain dan dapat juga memanipulasi orang lain. Orang-orang yang memiliki kekuasaan juga seringkali menggunakan kekuasaan untuk memuaskan nafsu seksual mereka. Michel Foucault (1978: 83) berpendapat bahwa jika kekuasaan hanya dilihat sebagai kemampuan untuk memiliki keinginan, atau jika konstitutif pada keinginan sendiri , untuk afirmasi: anda akan selalu dan sudah terjebak. Skripsi ini difokuskan pada kekuasaan dan seksualitas Kurt Janisch di novel Greed oleh Elfriede Jelinek. Tujuan dari penelitian ini adalah untuk menggambarkan bagaimana kekuasaan Kurt Janisch yang digambarkan dalam Greed oleh Elfriede Jelinek, dan untuk mengungkapkan bagaimana kekuasaan Kurt Janisch mempengaruhi seksualitasnya. Skripsi ini menggunakan beberapa proses analisis, yaitu: (1) mengklasifikasikan kutipan yang relevan dan sesuai dengan rumusan masalah, (2) menggambarkan kekuasaan Kurt Janisch dengan menggunakan teori five bases of power oleh John RP French dan Bertram Raven , (3) mengungkapkan bagaimana seksualitas Kurt Janisch dipengaruhi oleh kekuasaannya dengan menggunakan circles of sexuality oleh Dr Dennis M. Dailey. Akhirnya, hasil analisis menunjukkan bahwa dalam novel ini Kurt Janisch menyalahgunakan kekuasaannya. Dia menggunakan setiap kesempatan yang ada untuk memaksa orang dan mengintimidasi rekan-rekannya yang lebih muda. Dapat dikatakan bahwa ia menggunakan kekuasaannya secara paksa – itu termasuk dalam coercive power. Selain itu, perilaku Kurt Janisch dalam mengintimidasi rekan-rekannya yang lebih muda dapat diklasifikasikan sebagai legitimate power. Dia juga menggunakan jenis informational power karena ia menyembunyikan informasi yang dapat membahayakan dirinya. Dengan kekuatan yang dimilikinya, ia memaksa perempuan untuk berhubungan seks dengannya. Saat berhubungan seks dengan wanita, Kurt Janisch melakukan beberapa kekerasan seksual, pelecehan seksual kepada anak, dan perkosaan yang termasuk dalam lingkaran sexualization. Fakta-fakta tersebut adalah bukti bahwa Kurt Janisch menyalahgunakan kekuasaannya untuk mendapatkan kepuasan dalam hubungan seksual. Kata Kunci: Kekuasaan, Seksualitas, Greed, Circles of sexuality Abstract Power is often defined as the capability of someone strong to achieve his desires over the will of powerless people. Powerful people can use their power to take advantage for themselves, control people can even manipulate someone else. Powerful people also oftenly use power to satisfy their sexual appetite. Michel Foucault (1978: 83) argues that if power is seen as having only an external hold on desire, or, if it is constitutive of desire itself, to the affirmation: you are always-already trapped. This study focuses on Kurt Janisch’s power and sexuality in Elfriede Jelinek’s Greed. The purposes of this study are to describe how Kurt Janisch’s power is depicted in Elfriede Jelinek’s Greed, and to reveal how Kurt Janisch’s power affects his sexuality. This study does some processes of analysis, they are: (1) classifying the relevant quotations which are in line with the problem of statements, (2) describing Kurt Janisch’s power by using the theory of five bases of power by John R.P. French and Bertram Raven, (3) revealing how Kurt Janisch’s sexuality is affected by his power by using Dr. Dennis M. Dailey’s circles of sexuality. Eventually, the result of the analysis shows that Kurt Janisch power which is depicted in the novel is abusive. He uses every opportunity that he has to force people and intimidate his younger colleagues. It can be said that he uses his power coercively–it is the coercive power. Moreover, his behaviour in pressing his younger colleagues is classified as legitimate power. He also uses the kind of informational power because he hides informations that can harm him. With the power that he has, he forces women to have sex with him. While having sex with women, Kurt Janisch does some sexual violence, child abuse, rape and sexual harassment which are included in the sexualization circle. Those facts are proofs that Kurt Janisch is abusing his power to get his only satisfication in sexual intercourse. Keywords: Power, Sexuality, Greed, Circles of Sexuality INTRODUCTION Power is often conceptualised as the capacity of powerful agents to realise their will over the will of powerless people, and the ability to force them to do things which they do not wish to do. Power is also often seen as a possession, something which is held onto by those in power and which those who are powerless try to wrest from their control. In The History of Sexuality, Vol. I, Michel Foucault argue that if power is seen as having only an external hold on desire, or, if it is constitutive of desire itself, to the affirmation: you are always-already trapped. Moreover, one must not imagine that this representation is peculiar to those who are concerned with the problem of the relations of power with sex. (Foucault, 1978: 83). The act of using one’s position of power in an abuse way is called power abuse. This can take many forms, such as taking advantage of someone, gaining access to information that shouldn’e be accesible to public, or just manipulating someone with the ability to punish them if they don’t comply. Abuse is the improper usage or treatment of an entity, often to unfairly or improperly gain benefit. Abuse can come in many forms, such as: physical or verbal maltreatment, injury, assault, violation, rape, unjust practices; crimes, or other types of aggression. Abuse of power is different from usurpation of power, which is an exercise of authority that the offender does not actually have. Sexuality is complex and spans a vast array of human experiences including family relationships, dating, sexual behavior, physical development, sensuality, sexualization, reproduction, gender, body image and more. It is a fundamental and natural part of being human, for people of all ages. Defining sexuality can be difficult, but it may help to think about Amy Schalet’s description of sexuality as posted on medscape.com, “as the expression of an age-blind desire for meaningful intimacy and connection with others”. Sexuality is much more than sexual feelings or sexual intercourse. It is an important part of who a person is and what she or he will become. It includes all the feelings, thoughts and behaviors of being female or male, being attractive and being in love, as well as being in relationships that include sexual intimacy and physical sexual activity. Jelinek’s works are mostly concern on patriarchal hierarchies define the engines of commerce and commerce defines personal relationships, its individuals’ sexuality. Besides The Piano Teacher and Women as Lovers, Greed is also regarded as one of her novels which concern on sexuality. So, this thesis will analyse Elfriede Jelinek’s Greed in the terms of its sexuality. In Greed, Kurt Janisch has a big power over the country. Unfortunately, he uses his power to harm and threaten other people. Kurt Janisch is a greedy and ambitious man. He likes to have many properties. But the way he try to get it is so nasty. He uses his power as a country policeman to get properties. He is somehow uses his power abuse. At one time, he would like to have a drink without paying it. According to him, he does not need to pay the drink because he has an authority there. Kurt Janisch realizes that he has a big power. His power is, however, influence his sexuality. He would like to have sex with women in his country just to have their properties. The women, who realize that Kurt is a powerful man, can not reject his attitude. He sometimes stop a woman for speeding then have sex with her beside her car. After that, they went to her house and Kurt can have that woman’s property. In accordance of background study above, it can be simplify to discuss among two problems that emerge as significant concern toward this novel. How is Kurt Janisch’s power depicted in Elfriede Jelinek’s Greed? How does Kurt Janisch’s power affect his sexuality in Elfriede Jelinek’s Greed? This study will uses two theories which are in line with the statement of the problems. The first problem is how Kurt Janisch’s power depicted in Greed. This statement will use the concept of power. This concept is originally introduced developed by social pschologists named French and Raven. This concept is united and merged with the bases of social power which people use in their daily life. There are five kinds of power in this concept, they are coercive power, reward power, legitimate power, referent power and expert power. There is also an additional kind of power, which is the informational power. Then the second problem is how Kurt Janisch’s power affects his sexuality. This statement will apply the concept of sexuality, especially in the circles of sexuality. This concept is developed by a man known as the pornographic professor, Dr. Dennis M. Dailey. It is about the circles of sexuality which is experienced by every human being. There are five circles, they are sensuality, sexual intimacy, sexual identity, reproduction and sexualization. RESEARCH METHOD Research methodolgy that used in this analysis here must be qualified as an applying in literary appreciation. The thesis is regarded as a descriptive-qualitative study and uses a library research. This study uses novel of Elfriede Jelinek entitled Greed that published Seven Stories Press, 140 Watts Street, New York in 2007 as the data source of this study. The datas are in the form of direct and indirect speech of the characters, dialogues, epilogues and quotations which indicate and represent aspect of power abuse and sexualization which is experienced by the main character. This thesis is using the library method in collecting the data. It does not use the statistic method. That is why it is not served in numbering or tables. Library research used an approach in analyzing this study. The kind of library research which is used here is intensive or closely reading to search quotations or phrases. It also used to analyze the literary elements both intrinsic and extrinsic. The references are taken from library and contributing ideas about this study from internet that support the idea of analyzing. The analysis is done by the following steps: (1) Classification based on the statement of the problems. This classification is used to avoid the broad discussion. There are two classifications in this study. They are the depiction of power and how it affects the sexuality. (2) Describing Kurt Janisch’s power which is stated from the quotations or statements. (3) Describing how Kurt Janisch’s sexuality which is stated from the quotations or statements. (4) Revealing the relations between power and sexuality. The quotations that showed how the character’s sexuality is affected by his power are taken as data. (5) Drawing the conclusion based on the analysis which is in line with the problems. ANALYSIS The first section is about the describtion of Kurt Janisch’s power as a country policeman. Kurt Janisch, the country policeman, is the main character in this story. For three generation, his whole family hold the power over the country. His father is a former police colonel while his son, Ernst Janisch, is employed by the Post Office as a telephone maintenance man. He attended a technical secondary school, whose graduates call themselves engineers. Being a country policeman makes Kurt Janisch hold a big power over his people. “Such a forceful, big man, who is capable of unleashing almost any kind of event.” (Jelinek, 2007: 10). Kurt Janisch is described as a forceful man. This is deal with his job as a country policeman. He has quite an authority to control people in his country so he is also described as a ‘big man’. He knew that he is the one who is more capable of making any decisions in his country and the people must live with his decisions. People mostly obey the figure of authority because they have been conditioned to do so. In this case, Kurt Janisch is in a position of power, so they are required to do so by law. Most citizens are afraid to disobey laws because they don't like the outcome or the embarrassment. The country policeman then uses his power to force his people. He forces everyone to get what he wants. From the way Kurt Janisch is described as a forceful man in using his power, it is shown that Kurt Janisch uses the kind of coercive power. As mentioned by French and Raven in the previous chapter, coercive power happens when a powerful man forces other people to do something they do not want to do (French and Raven, 1959: 87). In this case, Kurt Janisch forces his people (mostly women) to do sex and give him their properties. The behaviour of Kurt Janisch can be classified in coercive power because he is also ‘capable of unleashing any kind of event’. It might be true that he is doing his job well by helping his people in any kind of situation. But on the other side, the word ‘any kind of event’ means that he can unleash people who is guilty by giving him somtehing in return. For Kurt Janisch, he only wants sex or properties. People are forced by him to do so, and they did it because they are powerless and have no other choices. Not only unleashing any kind of event, he could also ‘create’ event so that he would get what he wants. Kurt Janisch is sometimes also in charge of maintaining traffic order. Once in a while he stop the car and inspect it. He thinks, he will get a slight advantage from it. “The country policeman only has to take advantage of the opportunity, because in their own car everyone makes a mistake once.” (Jelinek, 2007: 44). He believes that the termination of some cars, there will be some drivers who commit traffic offenses. They could be not carrying the driving license or they could even carrying drugs. If there is an offense, then he will offer them some choices. Such things like he will give him a ticket or they can give him a bribe. As a country policeman, Kurt Janisch may stop and search any person or vehicle for stolen or prohibited things. Generally weapons such as knives and guns that are made or adapted for use in accordance with certain offences which include fraud, criminal damage, theft, burglary and taking a motor vehicle without authority. But a police officer cannot simply stop and search anybody he likes. In this case, Kurt Janisch has proven that he is abusing his power. He stop and search without any reasonable grounds and he even take advantages from it. He can do this just because he has a warrant card which he shows them everytime he do stop and search. It makes people do not dare to reject him. Since Kurt Janisch has a greedy nature, he uses any ways to satisfy his ever-increasing demands. Because he is a country policeman, then he can use his power to fulfill his greediness. One of his ways is force women to give him properties. “His fingers are itching to angrily beat the woman if she doesn't want to give up her house voluntarily,” (Jelinek, 2007: 278). There is no word ‘to give up’ in the Kurt Janisch’s dictionary in getting properties. Therefore he does not hesitate to use violence to get it. In this sentence, it can be seen that Kurt Janisch had thought that he would hit the woman if she refused to give her home. However, he also forced her to hand it over voluntarily. It does not matter whether she is really voluntary or not. The important thing to him is that people know that she gave her house voluntarily. The forcing behaviour that Kurt Janisch did in getting a house can be classified in coercive power. He uses his power to force someone to do what he wants. He did not hesitate to commit coercion because he knew that he is powerful. Therefore, the people will not dare to report him. This action can also be called as an abuse of power. The effect of abuse of power in the government is that the citizens suffer. When the government abuses their power, the society cannot benefit as it properly should because those in position to help are not staying within the realm of their job. Kurt Janisch is not only misusing his power to his people in his district. People in his office also admitted that he is quite powerful. “He is otherwise something of a disrespectful man, the country policeman, and so he demands all the more respect from the young recruits.” (Jelinek, 2007: 195). Kurt Janisch is always look nice and warm in front of the women. But to his co-workers, he is described as a disrespectful man. He likes to putting someone down, trying to make them feel low and treating someone in a horrible manner. Sometimes he is also showing his co-workers that they mean less than nothing to him. He is both rude and ignorant towards another persons feeling. This behaviour is shown by Kurt Janisch mostly to the young recruits. He asked them to show him more respects. While in fact, he does not respect them as much as they do. He thinks that it should be the way, since he is a senior and they were just a young recruiter. What Kurt Janisch does to his young recruiters is included to legitimate power category. A leader who has ability to control other people’s feeling by giving them rewards or punishment is a kind of leader in legitimate power. They can give them rewards or punishment to anyone. They also can do anything to them as punishment. The subordinates have no right to reject the rewards or punishments which the leader gives. According to French and Raven in this legitimate power theory, Kurt Janisch’s subordinates will only obey him as a country policeman not spesifically in person. This power is therefore not strong enough to be Kurt Janisch's only form of influencing or persuading. Even so, he keeps doing it. For him, it is a matter of pride. “he will take every opportunity to press up against younger colleagues, to pass his hands over their hips and to let them properly feel his little fellow,” (Jelinek, 2007: 298). From the sentence above, we can see that Kurt Janisch is sometimes does not hesitate to commit physical violence against his younger colleagues. Once his younger colleagues are making mistakes, he would give them some lessons rudely. He treated them that way in order to make sure that the will not do the same mistake twice. But somehow he became too far. It is shown that he would use every opportunity he has to press up his younger colleagues. However, he press up his colleagues violently. He put his hands around their hips and punch it. He punches them quite strong so they can feel how dissappointed he is. He thinks, if he do it that way, they will learn something. Kurt Janisch is granted many powers in order to keep the peace and protect the general public. There are, of course, limits on his behaviour and if people feel he has used unlawful practices, they should contact a lawyer for legal advice. But Kurt Janisch does not get any complaints for all his behaviors which are beyond the limits. “They have the power to make people disappear without trace forever.” (Jelinek, 2007: 261). In addition to maintaining security and protecting the public, Kurt Janisch also sometimes assigned as an investigator. He admitted that policemen have a big power in almost everything. It is shown in the sentence above that they can make people disappear without any trace left. It means that he could kill people and no one will know that he is the culprit. He could use his power as an investigator to throw all the evidences. So people would not know how the victim died and who did it forever. For this, Kurt Janisch uses his power as informational power. He holds an information and he manipulated it to his people. Informational power is based on the potential to use information. Providing rational arguments, using information to persuade others, using facts and manipulating information can create a power base. In this case, Kurt Janisch is keeping the information secretly and even organizing it neatly as if nothing happened. Then, the second section will show the effects of power in Kurt Jansich’s sexuality in the novel. Sexuality is also become the main idea in this novel. The country policeman is already married, but his sexual life with his wife does not appear much in this novel. However, his sexual life with other women is much exposed. It is so much easier for him to get any women when he comes in as a figure of authority. “These female proceedings have to be conducted and intimately handled, even if what the Janischs do is not described like that. They combine the pleasing with the useful.” (Jelinek, 2007: 26). Everytime Kurt Janisch helps women, he proceeded them ‘differently’. Not only him, but his son is also joining him in handling the women. People believed that both of them are treated them unfairly. However, the Janischs have their own argument. They think of it as give-and-take. Whenever they help women, those women have to please them. Kurt Janisch is the one who is quite influential here. He uses his power to manipulate women in his sexual experiences. His act of control and influence women unfairly means that he is in a sexualization cycle. In this cycle, people can do things like flirting or even rape to get what they want. It can cause the women to feel shame and humiliation, but since he is a country policeman, they can not do nothing about it. “What interests the country policeman about women also lies more below the waistline,” (Jelinek, 2007: 199). Kurt Janisch is really do not care anything else when his lust is appearing. He's not interested in what she says. He's interested in what she has. More importantly, he is very interested in the women’s organ right under their waistline. He thinks that if he can control their vagina, he can control her completely. He knows that once a lonely woman has been satisfied, he will get what he wants more easily. People in various professional and institutional settings endure many forms of unwanted sexual acts that are perpetrated against them by people in positions of power. These perpetrators abuse their power, authority, trust, influence, and dependence to obtain sexual intercourse. (Buchhandler and Raphael, 2010: 3). The act that Kurt Janish has been done is somewhat an act of disrespectful through women. Women needs to be taken care and be loved. Men are using sex instrumentally in order to obtain and retain power over women. An evolutionary perspective does not deny the linkage between power and sex but suggests that the direction of causation is misperceived. Rather than men using sex to obtain power, it is much more accurate to say that they use power to obtain sex. (Browne, 2006: 147). Even they are being treated harshly and disrespectful, these women did not protest or report. Most of them are even delighted that they can have sex with a country policeman. “Two legs spread, for him alone, just like that, and a whole house puts in an appearance right in the middle.” (Jelinek, 2007: 117). It is easy for Kurt Janisch to get what he wants. With the power that he has, he only needs two legs spread, like it is stated on the sentence. It means that he can conquer and persuade women to have sex with him. Once the women were already conquered, then they will give him whatever he wants. This makes Kurt Janisch addicted. When he realized that he could get what he wants so easily, then he will do it continously. However, to get two legs spread, Kurt Janisch is forcing them to do so. This behaviour can be classified in the coercive power. It is so, because Kurt Janisch is forcing the women to act in an involuntary manner by use of intimidation and threats. Coercion is one method by which a powerful agent can exercise and maintain his dominance over another. When one has the power needed to credibly threaten another, one can use that power to impose one's will on her regarding many choices. In law, coercion is classified as a threat crime. Such actions are used as leverage, to force the victim to act in a way contrary to their own interests. Coercion may involve the actual infliction of physical pain or psychological harm. This act of coercion that has been done by Kurt Janisch in sex can also be called as the act of rape. Often those men who see women as sex objects and as inherently inferior to men are more likely to commit to rape. Men who hold these beliefs think that they are entitled to control women’s sexuality, and to determine what a woman really wants. Such men also think they are entitled to shape women’s sexual and nonsexual behavior, and to decide what is acceptable or unacceptable. Therefore, women should meet male needs on demand, men are entitled to force their desires onto women, and therefore, men are entitled to rape women. (Lowell, 2010: 160). Sexual abuse of power, like rape, constitutes serious harms to victims precisely because it typically violates these rights. The right to remain free from sexual coercion stands at the basis of these violations: sexual coercion occurs whenever a person engages in unilateral sexual acts with another person, by exploiting that other person’s body for the purposes of his own gratification, arousal or one–sided sexual pleasure, against the will of that other person. A little blood is coming from her vagina. What has he stuck in there this time, bigger than a slap in the face, smaller than a tractor? Perhaps the neck of the beer bottle? (Jelinek, 2007: 82) Not only described as a forceful man when it comes to sex, but he is also described as a crude person. It is stated in the sentence above that after having sex with a girl, a little blood is coming from her vagina. She also feels a great painful when she woke up. She wonders why is that happen. It was not the first time she has sex, so it is obviously not a virgin blood. It can happen because of two things. Either she was on her period or Kurt Janisch was hardly forces his cock into her vagina. From the sentence, the right answer is the second one. She is wondering what he stuck in her vagina. The pain feels more painful than a slap in the face. She presumes that he inserted the neck of the beer bottle which is very hard and painful. This is also the act of sexual assault that has been done by Kurt Janisch. it is the act of having intercourse while doing a physical violence or using a tool. It can cause a great painful, a wound and even a fatal injury. Sexual assault can also included in case of rape because Kurt Janisch forces his cock that cause her to feel great pain in her vagina. This time, he uses his overpowering strength to the woman. It is classified in the sexualization cycle because he once again use his power to manipulate and harm his victim. Like the other victims, this woman is afraid to report him to the police officer. Eventhough she dares to report him, Kurt Janisch will take care of the case. He is also capable to remove all the evidences so that her accusation will not be proceed. As a figure of authority, Kurt Janisch has done too many crimes in his country. Not only raping, but he also done such act like sexual violence. He is surely has a sexual problem. “he's blowing his trumpet into such a young girl, she's no more than a child,” (Jelinek, 2007: 83). Not enough with raping and sexual violence, he also dare to do a child abuse. It seems like his candidate for intercourse is not only adult women, but also a child. Through the statement above, we know that Kurt Janisch has an intercourse with a young girl who is described as no more than a child. This action can also be classified as raping. It was told in the story, an adult woman who has had sex with Kurt Janisch saw him having sex with a young girl. She was jealous and claimed that his trumpet is should be hers. Although Kurt Janisch has too many crimes, many women are still go after him. They all want to be treated by the country policeman. The fact that many women are after him, it makes him feels like he can own and control them. Moreover, he can control them because he is a country policeman. He did almost every crime in sexuality, like flirting, raping and even seduction. But his crimes are never been reported. His crimes are all covered by himself. He handles his own crime so nobody can jailed him. He is the one who can send people to jail and he obviously does not want to send himself. This is the power of authority, after one can control and manipulate someone, than everything can be done. Kurt Janisch has chosen to use his power to satisfy his need: sex. When his desire of sex is flaming, he would easily pick any woman to have sex with. His sexuality has become more complex lately. He would not care who the woman is, or does the woman wants it or not, he will just do it. “The age of the children is unimportant, they can be almost sixteen like Gabi,” (Jelinek, 2007: 128). It gets worsen when he started to choose a young girl as a place to release his lust. It turns out that he did not do it once. He chose Gabi, who is almost sixteen to be his victim. Kurt Janisch admitted that he does not care about her age, evethough he knows that she was almost sixteen which means that she is still under age. All he cares about is just he has some place to release his lust, so any women will do. Kurt Janisch is now got into a serious problem. His act of raping a girl under age can be classified as child sexual abuse. Child sexual abuse is fundamentally an act of violation, power and domination. The sexual abuser’s power, knowledge and resources are far greater thatn those of the child. So the abuser exploits this power difference to take advantage of the child. Children are dependent upon adults for their survival and for affection and understanding of the world. Kurt Janisch thinks that asking a girl who is in her puberty to have sex would be very easy. Girls that age are still fragile and tey can be easily manipulated. In this case, the one who manipulated her is someone who holds a big power over the country. This girl, who is known as Gabi, is just under sixteen. She is still innocent and easily trust any adults. That is why Kurt Janisch uses any tactics to get her. He gives her attention and gifts, manipulate and even threaten her. Gabi trusted him since he is the country policeman. But she never knew that he only wants her virginity. Kurt Janisch has done something terrible to Gabi. Girls at age 16 are emotionally unstable. He does not think that what he has done to her gave a big impacts in her life. Gabi does not want to let him go. She believed that she and Kurt Janisch has become a couple. But Kurt Janisch who only uses her as a relief from Gerti. He does not want that kind of relationship, so he dump her. Gabi becomes very depressed and aggressive. She still wants to be with him. However, she can not reported what Kurt Janisch has done to her. She was afraid to tell anyone. Besides, it was a shameful experience for her. So she just keep it to herself. CONCLUSION The conclusion is divided into two in accordance to the statement of problems. From the analysis that has been done, it can be conclude in the first conclusion that Kurt Janisch has a great power in the country. He is described as a forceful man because he oftenly forced people to do domething that he wants. People mostly obey him because they have been conditioned to obey the powerful people. Otherwise, people who disobey them will get a punishment. As a man who has power in his country, he tries to get any advantages he might get. He is powerful enough to get anything he wants from his people. He is described as a powerful man because he can unleash any kind of events. However, his way to unleashing any kind of events is by forcing people to have a sexual intercourse with him, otherwise, their driver’s license will be taken. Whenever he has an opportunity to take advantages, he would go for it. He will make an entrance as a figure of authority. He even forces people in a bar to give him free drinks because he said that he is on duty. While he is on duty as a traffic cop, he would also like to take advantages from the women drivers. He knows that women drivers are mostly make mistakes. So there he goes, stop and search them, threaten them and finaly forces them to give him what he wants. Kurt Janisch’s act of forcing people can be classified in coercive power. It can be seen that he oftenly forces people to do what they do not want to do. Besides using the coercive power, Kurt Janisch is sometimes also use the legitimate power. It is shown when he deliberately pressing up and beat his younger colleagues when they do mistakes and do notwant to obey him. He likes to show his seniority against his juniors in the police office. He wants to be respected, but he does not want to respect his colleagues. Kurt Janisch who is sometimes also in charge of search team uses the kind of informational power. He thinks that country policemen also have power to make people disappear without any trace left. He has the capability to hid and manipulate the information he gets to protect himself from any harm. That is why the crimes that Kurt Janisch’s done are never been proceed in the court. So, Kurt Janisch’s power that is described in this novel are very big. It can be said that Kurt Janisch is abusing his power. The second conclusion is about how Kurt Janisch power affects his sexuality. In the analysis chapter, it can be seen that Kurt Janisch likes to controlling another person in many cases. He also applied this act to have sex with women whom he forced. He likes to help women with their problems and ask them to have sex with him in return. The women can not refuse because they know that they are forced by someone with enormous power in their country. Since then, Kurt Janisch likes rough sex. He oftenly hitting the victim of both on the face and the mouth. This is the act of sexual violence. Then he also hurt the sex organs of a woman because he put his penis too hard. It causes the woman's vagina bleeding hard. In addition, he also did verbal violence by telling the women that they are just toys for Kurt Janisch which can be played at his will. The harshest thing that he did is child abuse. He raped an under-age girl named Gerti and Gabi and cause Gerti to commit suicide. All of his victims do not do any resistance. They have been threatened by Kurt Janisch to keep it. If they leak it, they will bear the severe consequences. Kurt Janisch can do violence to his victims because he feels that he is a powerful person. He can rule in all respects, including in sexual intercourse. In this case, he will not care about the effects that would arise from the sexual violence he was doing. The act of rape, sexual violence and sexual abuse can be classified in a circle sexualization. Sexualization is using sex or sexuality to influence, manipulate or control other people. So, with the power that he has, Kurt Janisch can easily rape any women and he likes to do rough sex. REFERENCE An Explanation of the Circles of Sexuality. Advocates for Youth. 2007. Web. November 27, 2013. < http://www.advocatesforyouth.org/for-professionals/lesson-plans-professionals/200> Barnett, Jordan. Kaplan’s Triphasic Model. Sex Wiki. April 11, 2011. Web. December 25, 2013. < http://sexual-communication.wikispaces.com/Kaplan%E2%80%99s+Triphasic+Model> Browne, Kingsley R. Sex, Power, and Dominance: The Evolutionary Psychology of Sexual Harassment. Detroit: Wiley InterScience, 2006. Buchhandler, Michal and Raphael. Sexual Abuse of Power. Selected Works. March 2010. Web. April 15, 2014. http://works.bepress.com/michal_buchhandler_raphael/9 Foucault, Michel. The History of Sexuality, Vol. I. New York: Pantheon Books, 1978. French, and Raven. The Bases of Social Power. Michigan: University of Michigan Press, 1959. Hutchinson, Paul L. and Gage, Anastasia J. Power, Control, and Intimate Partner Sexual Violence in Haiti. Archives of Sexual Behavior, Vol. 35, No. 1, 2006. Jelinek, Elfriede. Greed. New York: Seven Stories Press, 2007. Lowell, Gary. A Review of Rape Statistics, Theories, and Policy. Undergraduate Review, 6, 158-163. 2010. Schalet, Amy. Must We Fear Adolscent Sexuality?. Medscape Multispecialty. December 30, 2004. Web. December 18, 2013. http://www.medscape.com/viewarticle/494933 Wrobel, Szymon. Power, Subject and the Concept of Rational Action, in: A Decade of Transformation, IWM Junior Visiting Fellows Conferences, Vol. 8: Vienna, 1999.